2018
DOI: 10.1002/hep.30105
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen F Locus Adjacent Transcript 10 Overexpression Disturbs WISP1 Protein and mRNA Expression to Promote Hepatocellular Carcinoma Progression

Abstract: Recently, studies on transcriptome-proteome relationships have revealed mRNA/protein expression discordance for certain genes and speculated that protein posttranslational modification (PTM) may be involved. However, there is currently no evidence to support this hypothesis. Wnt-induced secreted protein-1 (WISP1) is the downstream target gene of β-catenin and plays an important role in tumorigenesis and progression, but the expression and role of WISP1 in different tumor types are controversial. Here, we first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…However, the over-expression of FAT10 resulted in a disorder of WISP1 mRNA and protein levels, with the expression of WISP1 protein decreasing and the mRNA expression of WISP1 increasing [80]. This study explained that FAT10 exerted its stabilization and degradation functions simultaneously by promoting WISP1 mRNA expression via stabilizing β-catenin yet directly targeting the WISP1 protein for degradation [80]. Nevertheless, there are converse results of FAT10ylation with tumor suppressor p53, whose reasoning remains unknown.…”
Section: Candidates Of Fat10ylation Cascadesmentioning
confidence: 99%
“…However, the over-expression of FAT10 resulted in a disorder of WISP1 mRNA and protein levels, with the expression of WISP1 protein decreasing and the mRNA expression of WISP1 increasing [80]. This study explained that FAT10 exerted its stabilization and degradation functions simultaneously by promoting WISP1 mRNA expression via stabilizing β-catenin yet directly targeting the WISP1 protein for degradation [80]. Nevertheless, there are converse results of FAT10ylation with tumor suppressor p53, whose reasoning remains unknown.…”
Section: Candidates Of Fat10ylation Cascadesmentioning
confidence: 99%
“…(42) Among the discussed mechanisms is the subsequent degradation of WISP1 and modification of Wnt signaling. (43) We noticed decreased protein levels of WISP1 in the liver of AMLN-fed animals but did not detect a significant up-regulation of the protein in response to our AMPK activator. This could be due to the high variability of the biological material, because we worked with whole-liver homogenates.…”
Section: Discussionmentioning
confidence: 52%
“…Aberrant WISP1 expression is associated with multiple solid human tumors and plays a pivotal role in tumorigenesis and progression (Liu et al 2019). Studies have shown that WISP1 is linked to colon cancer, oral squamous cell carcinoma, gastric cancer, breast cancer, esophageal cancer, prostate cancer, hepatocellular carcinoma and so on (Nagai et al 2011;Ono et al 2013;Chiang et al 2015;Gurbuz and Chiquet-Ehrismann 2015;Clausen et al 2016;Wu et al 2016;Yan et al 2018;Loftus et al 2020;Zhang et al 2019). Clausen et al (2016) noticed that WISP1 expression was regulated by DNA methylation and that WISP1 demethylation contributed to lymph node metastasis in patients with oral squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%